2013
DOI: 10.1364/oe.21.007196
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonically enhanced hot electron based photovoltaic device

Abstract: Hot electron photovoltaics is emerging as a candidate for low cost and ultra thin solar cells. Plasmonic means can be utilized to significantly boost device efficiency. We separately form the tunneling metal-insulator-metal (MIM) junction for electron collection and the plasmon exciting MIM structure on top of each other, which provides high flexibility in plasmonic design and tunneling MIM design separately. We demonstrate close to one order of magnitude enhancement in the short circuit current at the resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 15 publications
(19 reference statements)
1
60
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18] These hot electrons were utilized in various applications such as photocatalytic water splitting, [19][20][21][22][23][24][25][26] dissociation of H 2 molecules 7,8 and photovoltaic devices. 11,13,[27][28][29][30] In this study, we showed that hot electrons can be generated in Mn-doped quantum dots via efficient 'upconversion' of the energy of two excitons into a hot charge carriers with excess energy stored in the electron, showing the enhanced photocatalytic activity in H 2 production reaction. Such upconversion can be possible due to the very long lifetime (τ Mn~6 ms) of Mn excited state sensitized via rapid exciton-Mn energy transfer, which can serve as a long-lived intermediate state for the sequential two-step process leading to the generation of hot electrons.…”
Section: Introductionmentioning
confidence: 75%
“…[11][12][13][14][15][16][17][18] These hot electrons were utilized in various applications such as photocatalytic water splitting, [19][20][21][22][23][24][25][26] dissociation of H 2 molecules 7,8 and photovoltaic devices. 11,13,[27][28][29][30] In this study, we showed that hot electrons can be generated in Mn-doped quantum dots via efficient 'upconversion' of the energy of two excitons into a hot charge carriers with excess energy stored in the electron, showing the enhanced photocatalytic activity in H 2 production reaction. Such upconversion can be possible due to the very long lifetime (τ Mn~6 ms) of Mn excited state sensitized via rapid exciton-Mn energy transfer, which can serve as a long-lived intermediate state for the sequential two-step process leading to the generation of hot electrons.…”
Section: Introductionmentioning
confidence: 75%
“…This work predicted an optimized efficiency of 2.7% under AM 1.5 G illumination. The asymmetric hot electron generation in the top and bottom contacts can also be realized by creating LSPRs in one of the contacts [103,105,114,115]. It has been shown that asymmetric hot electron generation and enhancement of hot electron emission in Au-Al 2 O 3 -Au MIM diodes can be realized by reshaping the top metallic film contact into stripes [103] (Figure 3D an LSPR under TM illumination; therefore, the incoming light is mostly absorbed in the top contact.…”
Section: Free-space Photodetectorsmentioning
confidence: 99%
“…1 Due to the unique property, SPs can find applications in a broad range of science and technology, such as nonlinear optics, 2,3 nanoscale imaging, 4 photodetectors, 1,5-10 metamaterials, 11,12 photocatalysis, 13,14 photovoltaic devices, [15][16][17][18] and novel therapies. 19 Recently, a kind of compact metalinsulator-metal (MIM) photodetectors based on the SPsinduced hot electrons was proposed and fabricated.…”
Section: Introductionmentioning
confidence: 99%